Assessing the impact of COVID-19 on rural women and men in northern Ghana - Alvi, Muzna; Gupta, Shweta; Barooah, Prapti (International Food Policy Research Institute, 2021)
While the lockdown in Ghana due to COVID-19 was not as stringent or long as in other countries (at least up to June 2021), it has severely affected rural household incomes, including remittances. Almost three-quarters of households surveyed reported income loss due to the pandemic in Aug/Sep 2020. Use of savings, borrowing and asset sales were common. Women often relied on men’s savings as a coping strategy; government transfers were insignificant. Addressing COVID-19 in rural areas is hindered by a domestic water supply crisis. Approximately half of respondents reported being worried about water availability, changing their activities due to lack of water, not having enough drinking water, and not washing hands when necessary.